Design Model for Cooperative Management Learning Material Development in the Digital Era - Sri Sumiyati (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of learning materials in supporting learning processes and outcomes. This study aims to develop Cooperative Management Learning Materials in the Digital era. The research method used is the Borg and Gall R & D Model. The instruments used in this study were check lists, questionnaires, pretest and post test and expert test. The data analysis technique used is the post test results, the average student score, the results of validation by experts and field trials. The results of this study indicate that 1) The results of the UPBJJ UT Location Category of UPBJJ UT Bandung 21.1%, UPBJJ UT Bogor 36.8%, UPBJJ UT Purwokerto 5.3%, UPBJJ UT Serang 15.8%, UPBJJ UT Surakarta 15.8% , Yogyakarta 5.3%, 2) the results of the Main Field Testing Model for the Design of Cooperative Management Learning Material Development in the Digital Era stated that the average was good/positive and very good/very positive, and 3) The results of the expert review stated the description of the material easy and understandable teaching.